PERAN DITKERSINHAN (DIREKTORAT KERJASAMA INTERNASIONAL PERTAHANAN) KEMENHAN DALAM KERJASAMA INDONESIA DENGAN NEGARA-NEGARA DI ASIA TENGGARA - ginanjar, Yusep (Universitas Jenderal Ahmad Yani, 2024)
Defense cooperation is something that is very important for Indonesia, especially when it begins to identify various potential threats through an outward looking view of the Indonesian defense system. In this situation, Indonesia needs to increase its defense cooperation with countries in Southeast Asia to fulfill its national interests, namely to establish regional stability as an effort to overcome various potential threats. In this situation, Southeast Asia is in the middle of the Indo-Pacific region which is very strategic and is always contested by major world powers, in this case the rivalry between the United States and China which want to spread their influence in the Indo-Pacific region. This research aims to look at the role of Ditkersinhan as a government institution in Indonesia which is fully responsible for international defense cooperation, specifically in the role of defense cooperation with countries in Southeast Asia. This research uses a qualitative-descriptive approach using literature study and interview data collection techniques. The results of this research show that Ditkersinhan plays a very active role in all defense cooperation carried out by Indonesia, for which Ditkersinhan has responsibility from the opening of the cooperation dialogue to the preparation of the draft agreement which is the result of the cooperation carried out. Ditkersinhan's role is said to be effective as proven by the large number of defense collaborations carried out by Indonesia with countries in the Southeast Asia region.